Effect of oxidative factor on quality of Frizian-holeshtine bull frozen- thawed semen and after thawed in different temperature and duration - .E.M.K, AL-Najar; .H.F.M, AL-Shemmary (Journal of Kerbala for Agricultural Sciences, 2018)
The aim of the study is to evaluate the effect of oxidative factors on sperm quality (motility, viability, and abnormality) through the estimation of enzymatic antioxidant Superoxide dismutase (SOD) , Glutathione peroxidase (GPx) , and Total antioxidant capacity (TAC). And oxidative marker Malondialdehyde (MDA), and 8-Hydroxydeoxyguanosine (8-OHdG) in different thawing temperature and duration (37ºc for 30secnd as control group , 40ºc for 20second and 50ºc for 10second) to determine the optimum temperature and duration which improve the seminal quality and developed the ability of fertilization during Artificial Insemination(AI). The semen was collected from the Frizian-holeshtine bull in Abo-Graib AI center then; they have been diluted, packed, cooled and frozen according to the protocol of AI-center. 30 straws of each bull was supplied and divided in to 3 group to conduct physiological and biochemical test. The physiological had been conducted to determine the effect of thawing state of semen on the (Motility%, Viability%, and Abnormalities %). Biochemical test had been conducted on seminal plasma to measure (SOD, GPx, TAC, MDA, 8-OHdG).The result show significant increase (p<0.01) in the viability and motility (p<0.05) and significant decrease in abnormality , MDA and 8-OHdG concentration in thawing state of (50°c for10second) compared with control state (37ºc for 30second) which demonstrated high significant increase in motility, abnormalities and (MDA, 8-OHdG , SOD , GPx and TAC) concentration. Also the study show negative correlation between (MDA, 8-OHdG) and motility, viability and negative correlation with abnormalities . Also show that there was positive correlation between (SOD, GPx, TAC) with viability and motility and negative correlation with abnormalities.